How dry is dry? Molecular mobility in relation to thallus water content in a lichen. (9th November 2020) - Candotto Carniel, Fabio; Fernandez-Marín, Beatriz; Arc, Erwann; Craighero, Teresa; Laza, José Manuel; Incerti, Guido; Tretiach, Mauro; Kranner, Ilse
Abstract : Analysis of molecular mobility and xanthophyll cycle activity in dehydrated lichen thalli allows assessment of the water content at which the transition from a liquid to a 'glassy' state occurs. Abstract: Lichens can withstand extreme desiccation to water contents of ≤ 0.1 g H2 O g –1 DW, and in the desiccated state are among the most extremotolerant organisms known. Desiccation-tolerant life-forms such as seeds, mosses and lichens survive 'vitrification', that is the transition of their cytoplasm to a 'glassy' state, which causes metabolism to cease. However, our understanding of the mechanisms of desiccation tolerance is hindered by poor knowledge of what reactions occur in the desiccated state. Using Flavoparmelia caperata as a model lichen, we determined at what water contents vitrification occurred upon desiccation. Molecular mobility was assessed by dynamic mechanical thermal analysis, and the de- and re-epoxidation of the xanthophyll cycle pigments (measured by HPLC) was used as a proxy to assess enzyme activity. At 20 °C vitrification occurred between 0.12–0.08 g H2 O g −1 DW and enzymes were active in a 'rubbery' state (0.17 g H2 O g −1 DW) but not in a glassy state (0.03 g H2 O g −1 DW). Therefore, desiccated tissues may appear to be 'dry' in the conventional sense, but subtle differences in water content will have substantial consequences on the types of (bio)chemical reactions that can occur, with downstream effects on longevity in the desiccated state.